1986
DOI: 10.1128/aac.30.5.798
|View full text |Cite
|
Sign up to set email alerts
|

Survey of anaerobic susceptibility patterns in Canada

Abstract: The in vitro activity of penicillin, cefoxitin, moxalactam, ticarcillin, clindamycin, chloramphenicol, and metronidazole against 590 anaerobic isolates collected from five Canadian hospitals during 1984 was determined by an agar dilution technique. Cefoxitin, clindamycin, chloramphenicol, and metronidazole were very active against most of the isolates. No major regional differences in the susceptibility patterns were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
1

Year Published

1989
1989
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
2
13
1
Order By: Relevance
“…The incidence of clindamycin resistance in the B. fragilis group has been reported by several investigators (1,8,20,22), although there is considerable variation in the resistance rates observed in different surveys, ranging from very low (0.6%, Bourgault et al [2]) to moderate (7%, Tally et al [24], and 10%, Derriennic et al [10]) to high resistance rates similar to ours (about 20% clindamycin resistance [1,9,19,21]). …”
mentioning
confidence: 69%
“…The incidence of clindamycin resistance in the B. fragilis group has been reported by several investigators (1,8,20,22), although there is considerable variation in the resistance rates observed in different surveys, ranging from very low (0.6%, Bourgault et al [2]) to moderate (7%, Tally et al [24], and 10%, Derriennic et al [10]) to high resistance rates similar to ours (about 20% clindamycin resistance [1,9,19,21]). …”
mentioning
confidence: 69%
“…3-lactamase-negative strains was 2 ,ug/ml; that for 3-lactamelaninogenicus (two), B. intermedius (one), F. mortiferum mase-positive strains was 8 ,ug/ml (Tables 3 and 4 (5). Other recent studies did not find any penicillin-resistant fusobacteria in 31 strains studied (7,16,23 ,ug/ml.…”
mentioning
confidence: 72%
“…,-Lactamase production has been reported for several non 19,26,29,30). ,B-Lactamase positivity has also recently been described in fusobacteria, notably, Fusobacterium nucleatum (5,31 32 ,ug/ml; 9 of these 10 isolates were ,-lactamase positive.…”
mentioning
confidence: 99%
“…Amoxicillin, temafloxacin, and clindamycin inhibited all 44 13-lactamase-negative strains (MICs for 90%o of the strains tested, <2.0 ,ug/ml). BRL 42715 will not be developed, but temafloxacin merits clinical evaluation.,B-Lactamase production and concomitant resistance to many ,B-lactams are usually encountered in the Bacteroides fragilis group but have been increasingly reported in other anaerobic gram-negative rods (2,6,7,13,14). We have examined the susceptibilities of 304 B. fragilis strains; 171 non-B.…”
mentioning
confidence: 99%